Effects of Resistance Exercise on Cerebral Redox Regulation and Cognition: An Interplay Between Muscle and Brain - Ricardo A. Pinho; Aderbal S. Aguiar; Zsolt Radák (MDPI AG, 2019)
This review highlighted resistance training as an important training type for the brain. Most studies that use physical exercise for the prevention or treatment of neurodegenerative diseases have focused on aerobic physical exercise, revealing different behavioral, biochemical, and molecular effects. However, recent studies have shown that resistance training can also significantly contribute to the prevention of neurodegenerative diseases as well as to the maintenance, development, and recovery of brain activities through specific neurochemical adaptations induced by the training. In this scenario we observed the results of several studies published in different journals in the last 20 years, focusing on the effects of resistance training on three main neurological aspects: Neuroprotective mechanisms, oxidative stress, and cognition. Systematic database searches of PubMed, Web of Science, Scopus, and Medline were performed to identify peer-reviewed studies from the 2000s. Combinations of keywords related to brain disease, aerobic/resistance, or strength physical exercise were used. Other variables were not addressed in this review but should be considered for a complete understanding of the effects of training in the brain.